Microbial infection risk predicts antimicrobial potential of avian symbionts - Martínez-Renau, Ester; Mazorra-Alonso, Mónica; Ruiz-Castellano, Cristina; Martín-Vivaldi, Manuel; Martín-Platero, Antonio M.; Barón, María Dolores; Soler, Juan José (Frontiers in Microbiology, 2022)
Symbiotic bacteria on animal hosts can prevent pathogenic bacterial infections by several mechanisms. Among them, symbiotic bacteria can indirectly enhance host’s immune responses or, directly, produce antimicrobial substances against pathogens. Due to differences in life-style, different host species are under different risks of microbial infections. Consequently, if symbiotic bacteria are somewhat selected by genetically determined host characteristics, we would expect the antimicrobial properties of bacterial symbionts to vary among host species and to be distributed according to risk of infection. Here we have tested this hypothesis, by measuring the antimicrobial ability of the bacterial strains isolated from the uropygial-gland skin of 19 bird species differing in nesting habits, and, therefore, in risk of microbial infection. In accordance with our predictions, intensity and range of antimicrobial effects against the indicator strains assayed varied among bird species, with hole- and open-nesters showing the highest and the lowest values, respectively. Since it is broadly accepted that hole-nesters have higher risks of microbial infection than open nesters, our results suggest that the risk of infection is a strong driver of natural selection to enhance immunocompetence of animals through selecting for antibiotic-producing symbionts. Future research should focus on characterizing symbiotic bacterial communities and detecting coevolutionary processes with particular antibiotic-producing bacteria within-host species.